2023
DOI: 10.1111/papr.13255
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal root ganglion stimulation for the treatment of chronic pelvic pain: A systematic review

Abstract: BackgroundChronic pelvic pain (CPP) is a difficult condition to treat. Due to complex pelvic innervation, dorsal column spinal cord stimulation (SCS) has not been shown to produce the same effect as dorsal root ganglion stimulation (DRGS) given emerging evidence suggesting that applying DRGS may result in favorable outcomes for individuals with CPP. The aim of this systematic review is to investigate the clinical use and effectiveness of DRGS for patients with CPP.Materials and MethodsA systematic review of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Recent studies have underscored the favorable outcomes of DRG-S neuromodulation compared to SCS across various conditions, including chronic pelvic pain, painful diabetic neuropathy, restless leg syndrome, and post-surgical or traumatic painful scars. These studies have demonstrated notable enhancements in quality of life, increased patient satisfaction, reduced medication dependency, and long-term cost-effectiveness [50][51][52][53]. Failed back surgery syndrome (FBSS) is usually refractory to conservative medical management.…”
Section: Clinical Applications Of Drg-smentioning
confidence: 99%
“…Recent studies have underscored the favorable outcomes of DRG-S neuromodulation compared to SCS across various conditions, including chronic pelvic pain, painful diabetic neuropathy, restless leg syndrome, and post-surgical or traumatic painful scars. These studies have demonstrated notable enhancements in quality of life, increased patient satisfaction, reduced medication dependency, and long-term cost-effectiveness [50][51][52][53]. Failed back surgery syndrome (FBSS) is usually refractory to conservative medical management.…”
Section: Clinical Applications Of Drg-smentioning
confidence: 99%